MUSICAL IDENTITY OF SOI PLAENG LAM TAD FROM THE PHO WANG TAE-MAE SRINUAN GROUP - Noisa-ard, Patcha; Leauboonshoo, Supunnee; Prateepchuang, Sarisa (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The objective of this article was to study the musical identity of Soi Plaeng Lam Tad from the Pho Wang Tae-Mae Srinuan group. The qualitative research methodology was used. Field data were collected from February to August 2022. The results indicated that Soi Plaeng Lam Thad is the opening song by one person appearing in the first part of Pho Phlaeng and Mae Phlaeng before the poem. The opening song of Soi Plaeng Lamthad is important because it is the main melody at the beginning that controls the song and determines the singer's pitch. Soi Plaeng Lam Thad consists of 5 melodies: Thamnong Klang, Thamnong Kraphue, Thamnong Mon, Thamnong Lao, and Thamnong Phama. The musical style is monophony. The melodic direction moves in the conjunct motion, the disjunct motion, 3 major intervals, 4 perfect intervals, 5 perfect intervals, and a stable style. The sound system is a major scale, Dorian mode, and major pentatonic. Quarter notes, eight notes, and eight-note dotted are mainly used in rhythmic patterns. The text setting is the monosyllabic word and melismatic text.